2023
DOI: 10.1038/s41467-023-36444-w
|View full text |Cite
|
Sign up to set email alerts
|

Faunal engineering stimulates landscape-scale accretion in southeastern US salt marshes

Abstract: The fate of coastal ecosystems depends on their ability to keep pace with sea-level rise—yet projections of accretion widely ignore effects of engineering fauna. Here, we quantify effects of the mussel, Geukensia demissa, on southeastern US saltmarsh accretion. Multi-season and -tidal stage surveys, in combination with field experiments, reveal that deposition is 2.8-10.7-times greater on mussel aggregations than any other marsh location. Our Delft-3D-BIVALVES model further predicts that mussels drive substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Mean sediment accumulation rates measured by (Letzsch & Frey, 1980) on Sapelo Island were highest in the low marsh zone (0.9 cm yr −1 ), which experiences the longest inundation period and supports higher density mussel populations, relative to transitional (0.45 cm yr −1 ) and high marsh (0.1 cm yr −1 ) zones. Amplified sedimentation via mussel suspension feeding and biodeposition, as seen in our Dean Creek study alongside others (Crotty et al., 2023), is likely an important mechanism underpinning the allochthonous shift we measured in accumulated OM, suggesting that the mussel effects we observed at the sediment‐water interface (i.e., increased benthic‐pelagic coupling and sedimentation) persist into the sediment layer.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Mean sediment accumulation rates measured by (Letzsch & Frey, 1980) on Sapelo Island were highest in the low marsh zone (0.9 cm yr −1 ), which experiences the longest inundation period and supports higher density mussel populations, relative to transitional (0.45 cm yr −1 ) and high marsh (0.1 cm yr −1 ) zones. Amplified sedimentation via mussel suspension feeding and biodeposition, as seen in our Dean Creek study alongside others (Crotty et al., 2023), is likely an important mechanism underpinning the allochthonous shift we measured in accumulated OM, suggesting that the mussel effects we observed at the sediment‐water interface (i.e., increased benthic‐pelagic coupling and sedimentation) persist into the sediment layer.…”
Section: Discussionsupporting
confidence: 84%
“…(2017) observed that organic C burial was positively correlated with within‐reef live oyster ( Crassostrea virginica ) density, attributing this relationship to increasing suspension feeding and baffling by reef structure (i.e., sedimentation) as well as shell production. Thus, we expect that density‐dependent sedimentation, which is also positively correlated within mussel aggregations (Crotty et al., 2023), is likely driving the continuous increase in accumulated C and N. Although previous modeling efforts suggest that mussel populations drive sediment deposition and vertical accretion at both creekshed (∼2,500 m 2 ) and landscape (∼10,000 m 2 ) scales as their biodeposits are dispersed across the salt marsh platform (Crotty et al., 2023), our study revealed that density‐dependent effects on C and N accumulation was not upheld in adjacent, non‐mussel areas. One mechanistic explanation for this may be that organic fractions of biodeposits are more readily remineralized locally while mineralogical fractions more effectively redistribute across salt marsh platforms.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations